One-Pot Synthesis of Ni0.05Ce0.95O2−δ Catalysts with Nanocubes and Nanorods Morphology for CO2 Methanation Reaction and in Operando DRIFT Analysis of Intermediate Species - Igor Luisetto (MDPI AG, 2021)
The valorization of CO2 via renewable energy sources allows one to obtain carbon-neutral fuels through its hydrogenation, like methane. In this study, Ni0.05Ce0.95O2−δ catalysts were prepared using a simple one-pot hydrothermal method yielding nanorod and nanocube particles to be used for the methanation reaction. Samples were characterized by XRD, BET, TEM, H2-TPR, and H2-TPD experiments. The catalytic activity tests revealed that the best performing catalyst was Ni0.05Ce0.95O2−δ, with nanorod morphology, which gave a CO2 conversion of 40% with a selectivity of CH4 as high as 93%, operating at 325 °C and a GHSV of 240,000 cm3 h−1 g−1. However, the lower activation energy was found for Ni0.05Ce0.95O2−δ catalysts with nanocube morphology. Furthermore, an in operando diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) analysis was performed flowing CO2:H2 or CO:H2 mixture, showing that the main reaction pathway, for the CO2 methanation, is the direct hydrogenation of formate intermediate.